Erythema multiformas sociated with herpes virus: case report - Anibal Manrique A; Mayra Leiva G; Mitchelle Linares D; Yordan Martinez E; , Jean Carlo Mayta C (Horizonte Médico, 2016)
Erythema multiforme (EM) is a hypersensitivity reaction that affects the skin and/or mucous membranes, in response to infections, drugs, or other comorbidities. Presentation of EM can be Minor (Mild EM, characterized for presenting target lesions) or Major (Severe EM, that occurs also with mucous membranes involvement). The case of a 36 year old male patient presenting to emergency of HNAL with fever, malaise, itching and painful ulcer type lesions in oral cavity, multiple target lesions in upper and lower limbs, penis, and perianal region is reported. The diagnosis was EM Major. Ulcerous lesions in oral cavity and target lesions in hands were the most salient.